Kebijakan Pengelolaan Pertambangan Mineral dan Batubara Aceh - Bidang Kajian Kebijakan dan Inovasi Administrasi Negara PKP2A IV LAN (Jurnal Transformasi Administrasi, 2014)
This article is conducted by extracted from a literature review and fieldwork conducted by the center for research and education and training aparatur in National Institute of Public Administration. Law - Law on Governing Aceh (PA in Act) No. 11 of 2006 confirms the authority of the Government of Aceh, District / City managing natural resources in Aceh is in accordance with the authority which includes planning, implementation, utilization and supervision of business activities. They are carried out by applying the principles of transparency and sustainable development. Through a review of the literature and field study, that post-discharge LoGA no regulation of derivatives in the form of Qanun mining management, thus although Aceh has special autonomy status, but in the management of technically not necessarily be done autonomously. Similar with other local governments in Indonesia, the technical implementation of mining in Aceh still refers to the norms, standards, and guidelines nationally. There for the guidance and supervision of mining activities has not run optimally and discipline. The Government of Aceh has not been fully able to regulate mining activities without permission, discipline violations - violations of administrative and technical nature of the mining company, has not been fully able to suppress the mining companies to implement programs based on the needs of community empowerment and independence ekonomir (more of its cash and cash assistance). This study recommends that the government needs to establish Aceh Qanun (Regional Regulation) update on the management of mining; identifying and data collection on mining permits are located in the district that has not been obedient to the mining activity reporting, issuing policies to reinforce the implementation of corporate responsibility to the community economic empowerment kemandiran around in the form of entrepreneurship programs, and scholarships for the children around the mining area , and strengthen access to participation in the community supervision of mining activities.